Beta-alanine supplementation improves jumping power and affects severe-intensity performance in professional Alpine skiers - Gross, M.; Bieri, K.; Hoppeler, H.; Norman, B.; Vogt, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
Introduction: Supplementation with beta-alanine may have positive effects on severe-intensity, intermittent, and isometric strength-endurance performance. These could be advantageous for competitive alpine skiers, whose races last 45 to 150 s, require metabolic power above the aerobic maximum, and involve isometric muscle work. Further, beta-alanine supplementation affects the muscle force-frequency relationship, which could influence explosiveness. We explored the effects of beta-alanine on explosive jump performance, severe exercise energy metabolism, and severe-intensity ski-like performance. Methods: Nine male elite alpine skiers consumed 4.8 g/d beta-alanine or placebo for 5 weeks in a double-blind fashion. Before and after, they performed countermovement jumps (CMJ), a 90-s cycling bout at 110% VO2max (CLT), and a maximal 90-s box jump test (BJ90). Results: Beta-alanine improved maximal (+7 ± 3%, d = 0.9) and mean CMJ power (+7 ± 2%, d = 0.7), tended to reduce oxygen deficit (-3 ± 8%, p = .06) and lactate accumulation (-12 ± 31%) and enhance aerobic energy contribution (+1.3 ± 2.9%, p = .07) in the CLT, and improved performance in the last third of BJ90 (+7 ± 4%, p = .02). These effects were not observed with placebo. Conclusions: Beta-alanine supplementation improved explosive and repeated jump performance in elite alpine skiers. Enhanced muscle contractility could possibly explain improved explosive and repeated jump performance. Increased aerobic energy production could possibly help explain repeated jump performance as well.